Nanoscale Secondary Ion Mass Spectrometry determination of the water content of staurolite. (7th July 2022) - Azevedo‐Vannson, Samantha; Remusat, Laurent; Bureau, Hélène; Béneut, Keevin; Cesare, Bernardo; Khodja, Hicham; Jiménez‐Mejías, María; Roskosz, Mathieu
Abstract : Rationale: Staurolite is an important mineral that can reveal much about metamorphic processes. For instance, it dominates the Fe–Mg exchange reactions in amphibolite‐facies rocks between about 550 and 700°C, and can be also found at suprasolidus conditions. Staurolite contains a variable amount of OH in its structure, whose determination is a key petrological parameter. However, staurolite is often compositionally zoned, fine‐grained, and may contain abundant inclusions. This makes conventional water analysis (e.g., Fourier transform infrared (FTIR) spectroscopy or by chemical titration) unsuitable. With its high sensitivity at high spatial resolution, Nanoscale Secondary Ion Mass Spectrometry (NanoSIMS) is potentially a valuable tool for determining water contents in staurolite. However a calibration with relevant standards covering a large range of water content is required to obtain accurate and reliable analyses, because matrix effects typically prevent direct quantification of water content by SIMS techniques. Methods: In this study, a calibration for NanoSIMS analyses of water content by using minerals with crystallographic structures comparable to that of staurolite (i.e., amphibole and kyanite, an inosilicate and a nesosilicate, respectively) has been developed. Results: Water measurements in an inclusion‐free crystal from Pizzo Forno, Ticino, Switzerland, by FTIR spectroscopy (1.56 ± 0.14 wt% H2 O) and by Elastic Recoil Detection Analysis (ERDA) (1.58 ± 0.15 wt% H2 O) are consistent with NanoSIMS results (1.56 ± 0.04 wt% H2 O). Conclusions: This implies that our approach can accurately account for NanoSIMS matrix effects in the case of staurolite. With this calibration, it is now possible to investigate variations in water content at the microscale in metamorphic minerals exhibiting high spatial variability and/or very small size (few micrometers).